Secure Communications Processing for Distributed Languages - Abadi, Martın; Fournet, Cédric; Gonthier, Georges (Proceedings of the 1999 IEEE Symposium on Security and Privacy, 1999)
Communications processing is an important part of distributed language systems with facilities such as RPC (remote procedure call) and RMI (remote method invocation). For security, messages may require cryptographic operations in addition to ordinary marshaling. We investigate a method for wrapping communications processing around an entity with secure local communication, such as a single machine or a protected network. The wrapping extends security properties of local communication to distributed communication. We formulate and analyze the method within a process calculus.